Relationship between transformational leadership and employees’ job satisfaction among the academic staff of UiTM affiliate colleges / Ros Intan Safinas Munir, Ramlee Abdul Rahman and Ariff Md. Ab. Malik - Munir, Ros Intan Safinas; Abdul Rahman, Ramlee; Md. Ab. Malik, Ariff (Faculty of Administrative Science and Policy Studies, 2012)
Organizations are increasingly focusing on developing transformational leadership in their managers because it leads to better organizational performance. Transformational leadership is necessary to motivate others to do more than they originally intended and often even more than they thought possible. Transformational leadership includes such characteristics such: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Previous studies found that leadership styles are important organizational antecedents of job satisfaction. Instead of that, transformational leadership becomes increasingly valued in the workplaces especially in influencing employee job satisfaction. Job satisfaction is perceived as an employee‘s response to conditions surrounding work referring to pay, benefits, promotion, style of supervision, co-workers and job environment. Thus, the aim of this study was to examine the relationship between transformational leadership and employee’s job satisfaction. A total of 214 Academic Staff from five (5) Affiliated Colleges in Klang Valley participated. A self-administered questionnaire was used to collect the data. The correlation of the total scores employees’ job satisfaction and transformational leadership indicated a positive, linear and strong relationship (r=.725). Using another correlation method, regression analysis differently shows that intellectual stimulation is highest significant with employee’s job satisfaction while idealized influence is lowest significant. Thus, it is important to understand the characteristics of leadership towards employees’ job satisfaction since it will affect employees’ morale and performance. This study would assist be able to assist managers to improve their leadership skills as to enhance employees’s job satisfaction. Apart from that, management can incorporate these findings by shaping effective leader in such a way to enhance the overall level of job satisfaction of their employees.